1992
DOI: 10.2169/internalmedicine.31.1073
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility Antigens Associated with Behcet's Disease in Northern Han Chinese.

Abstract: Among Han nationality Chinese and living in the northern area of the Yellow River, 120 patients suffering from Beh^et's disease and 100 unrelated healthy individuals were typed for histocompatibility antigens (HLA)-A,-B,-C, and-DR and-DQ antigens. HLA-DR and DQ typing was performed on B-lymphocyte separated with Lympho-B-Kwik. The HLA-antisera were provided by llth IHWC. Bf alleles and C4 allotypes were determined by immunofixation agarose-gel electrophoresis. HLA-B51 was found in 67/120 (55.83%) patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…These studies have also revealed that the HLA-B51 phenotype is strongly associated with Behget's disease in these ethnic groups (6)(7)(8)(9)(10). Chajek-Shaul and coworkers have reported that neutrophil chemotaxis in patients with Behget's disease who possess the HLA-B51 antigen was significantly enhanced as compared with that in HLA-B51 negative patients (4).…”
mentioning
confidence: 99%
“…These studies have also revealed that the HLA-B51 phenotype is strongly associated with Behget's disease in these ethnic groups (6)(7)(8)(9)(10). Chajek-Shaul and coworkers have reported that neutrophil chemotaxis in patients with Behget's disease who possess the HLA-B51 antigen was significantly enhanced as compared with that in HLA-B51 negative patients (4).…”
mentioning
confidence: 99%
“…19 In China, there have been two previous studies; however, one is quite old, and not focusing on HLA class II, 23 the other has been analysed grossly by serological method and revealed no association between HLA class II antigens and BD. 20 In an analysis of 1500 In this study, the association between HLA-DRB1 alleles and clinical manifestations of BD was also evaluated. We found that the On the contrary, the frequency of HLA-DRB1*14 alleles was found to be significantly increased in BD patients with folliculitis-like lesions, and in BD patients with erythema nodosum-like lesions, indicating that HLA-DRB1*14 appeared to be associated with skin lesions and HLA-DRB1*14 might be the gene responsible for a susceptibility to develop folliculitis-like lesions and erythema nodosum-like lesions.…”
Section: Discussionmentioning
confidence: 99%
“…4 In an attempt to find the association of HLA class II gene with BD, a number of studies have been performed in different ethnic groups, but the results varied with different countries and regions. [14][15][16][17][18][19][20] In a previous study, association of HLA class II with Chinese BD has been analysed grossly by serological method. 20 Recently, the new HLA genotyping method named LABType TM SSO was developed and has enabled us to rapidly detect and type the HLA-DRB1 alleles with an accurate probability of greater than 99.9% and without ambiguities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic association of HLA-B5 (B51) with BD was initially reported in 1973 by Ohno and coworkers [24]. Subsequently this association has been confirmed in many different ethnic populations in Asia (Japanese [16,[24][25][26][27][28], Korean [29,30], Han Chinese [31], Taiwan Chinese [32], Turk [33][34][35][36][37], Israeli [38][39][40], Palestinian and Jordanian [41], Iranian [42], and Iraqi [43]), Southern Europe (Italian [44][45][46], Greek [47][48][49], Spanish [50], and German [17,51]), Northern Africa (Moroccan [55] and Tunisian [56]), North America (Mexican [59]), and South America (Brazilian [60]), but not in some populations in Northern Europe (British [35,52,53]) and North America (American [57,58]) ( Table 1). Although the odds ratio (OR) for the susceptibility risk of BD among carriers of HLA-B51 has been known to be much higher in the ethnic groups who live in endemic areas along the ancient Silk Road than in the American or British populations, recently published data have shown that the HLA-B51-associated risk could be significantly raised even among some other populations outside the ancient tradin...…”
Section: Mhc Genes (A) Hla-b51 Antigenmentioning
confidence: 98%